Development of cross-border tourist and recreational regions on the Karelian section of the Russian-Finnish border - Manakov, A. G.; Kondrateva, S. V.; Terenina, N. K. (Baltic Region, 2020)
Despite that fact that cross-border tourism and recreation in the Baltic Sea Region have been extensively studied, there are still areas, which require further research. The aim of this article is to identify regions having active cross-border tourism and recreation in the adjacent territories of Finland and the Republic of Karelia. The authors propose to use an indicator characterizing the volume of incoming tourist flows. The number of tourists is not only indicative of the development of cross-border tourism and recreation; it is also one of the main criteria for determining the degree of the formation of cross-border regions. Using the statistics for Finland, the authors analyzed the geography of tourism in Finland's border areas and identified the degree of intensity of cross-border tourism exchange between the neighbouring administrative units of the two countries. The article also examines other tendencies indicative of the formation and development of cross-border tourism and recreation regions along the Russian-Finnish border. The authors identified three cross-border tourism and recreation regions of different development levels: South Karelia, Middle Karelia and North Karelia. South Karelia is a mesoregion with the average annual tourist exchange of about 100 thousand people, which is the average level of tourism development. The total volume of cross-border tourist flows from and to other cross-border tourist and recreation regions is about 30 thousand people per year. Middle Karelia microregion ranks second and is followed by the North Karelian microregion. The authors conclude that these two microregions are at the initial stage of their formation and, therefore, can be regarded as parts of one microregion - Russian-Finnish Northern microregion.